Multifocal Plane Display Based on Dual Polarity Stereoscopic Metasurface. (17th October 2022) - Zhang, Xue; Li, Xin; Zhou, Hongqiang; Wei, Qunshuo; Geng, Guangzhou; Li, Junjie; Li, Xiaowei; Wang, Yongtian; Huang, Lingling
Abstract: Stereoscopic 3D display devices have been developed toward integration and compactness. Metasurfaces have immeasurable advantages in the field of 3D display due to their tiny structures and flexible design capabilities. Here, a 3D multifocal display method based on stereoscopic metasurface (SMS) is proposed and demonstrated. Based on Dammann optimization method and Fourier expansion with zone plate to generate phase profile, such SMS can reorganize different planar images projected from Digital Mirror Device to form 3D images with correct depth clues. Thanks to the large Numerical Aperture of nano‐devices, total 20 multi‐focal planes can be independently used for display by considering dual polarization multiplexing. The experimental effects for stereoscopic arrangement of 3D number, letters, and several 3D images are demonstrated. Such compact‐scale SMSs have great potential to the applications of augmented/virtual reality devices, stereoscopic optical engraving, 3D optical manipulation, etc. Abstract : In this study, a noval kind of stereoscopic metasurface (SMS) utilized Dammann optimization method is proposed, which produces multiple focal planes. Such SMS reorganizes different planar images to different diffraction orders to form 3D images with correct depth clues. The dual channel polarized modulation brings in mirror‐like stereoscopic visual effect.